Big data technology and applications : first National Conference, BDTA 2015, Harbin, China, December 25-26, 2015. Proceedings /: first National Conference, BDTA 2015, Harbin, China, December 25-26, 2015. Proceedings. (2016) - Unknown
No abstract available